A significant upsurge of body mass index in patients with chronic hepatitis C successfully treated with direct-acting antiviral regimens - Kassas, Mohamed El; Alboraie, Mohamed; Naguib, Mervat; Omar, Heba; Tahan, Adel El; Moaz, Inas; Abdellah, Mohamed; Ezzat, Sameera; Wifi, Mohamed-Naguib; Sherief, Ahmed F.; Eltabbakh, Mohamed; Abdelsalam, Lobna; et al. (Turkish Journal of Gastroenterology, 2019)
Background/Aims: There is less data regarding the changes in body mass index (BMI) after treating hepatitis C virus (HCV) patients with new direct-acting antiviral agents (DAAs). This study aimed to assess the changes in BMI in chronic HCV patients treated with DAAs in Egypt and to explore other factors influencing this change.Materials and Methods: The data of chronic HCV patients who received antiviral therapy with new DAAs in one of Egypt’s specialized viral hepatitis treatment centers were retrospectively analyzed. In addition to the routine clinical and laboratory workup, changes in body weight during and after treatment were monitored and BMI was calculated. Viral load was measured at 12 weeks post-treatment to assess a sustained virological response. Patients with documented thyroid abnormalities, bariatric surgery, or ensuing special diets were excluded. BMI of >30 was taken as the cutoff for pa¬tients with obesity.Results: The study included 162 patients with a mean age of 48.56±11.49 years, of whom 61.1% were males, 16% were treatment-experienced, 12% were diabetic, and 29% were obese. Treatment duration was 12 weeks in 84% of patients and 24 weeks in 16% of patients. There was a significant increase in BMI post-treatment as compared to pretreatment measures (28.68±5.35 vs 28.18±4.55) (p=0.03). BMI changes were constant regardless of cirrhosis or previous treatment experience.Conclusion: Treatment of chronic HCV with DAAs was associated with increased body mass index. Further studies are needed to explore if this effect is secondary to treatment with DAAs or is an improvement in the liver function and lifestyle of treated patients.